Economic Resilience in the Face of Global Crises: A Study on the Resilience of Modern Economic Systems - Lanori, Tamrin (PT. Anagata Sembagi Education, 2026)
Economic resilience has become a critical concept in understanding how modern economic systems respond to increasingly complex global crises, including financial instability, pandemics, and geopolitical disruptions. This study aims to analyze how macroeconomic policies, structural characteristics, and institutional quality interact in shaping economic resilience. The research employs a qualitative approach using a literature-based method, with data collected from reputable international journal articles published between 2020 and 2025. Data were analyzed using qualitative content analysis and thematic analysis to identify patterns and relationships among key resilience determinants. The findings reveal that credible fiscal and monetary policies play a fundamental role in stabilizing economies, while economic diversification and complexity enhance adaptive capacity and reduce vulnerability to shocks. Institutional quality strengthens policy effectiveness and coordination, whereas human capital and innovation contribute to transformative resilience by enabling long-term structural change. The discussion highlights that economic resilience is a multidimensional and integrative process, requiring synergy across macro, structural, and institutional dimensions. In conclusion, achieving sustainable economic resilience necessitates a holistic and forward-looking approach that emphasizes adaptability, innovation, and systemic transformation in response to global uncertainties